2023
DOI: 10.1002/anie.202305155
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Protein Mediated Formation of the Dihydropyridazinone Ring in Actinopyridazinone Biosynthesis

Abstract: Heterocycles with nitrogen‐nitrogen (N−N) bonds are privileged building blocks of synthetic drugs. They are also found in natural products, although the biosynthetic logic behind them is poorly understood. Actinopyridazinones produced by Streptomyces sp. MSD090630SC‐05 possess unique dihydropyridazinone rings that have been studied as core nuclei in several approved synthetic therapeutics. Herein, we performed gene knockouts and in vitro biochemical experiments to elucidate the major steps in actinopyridazinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We reasoned that putative FAD-dependent oxidoreductase Afn7 could be responsible for this step, catalyzing a C–N bond cleavage reaction utilizing 12 (Figure S15). Homologues of Afn7 have been shown to catalyze analogous transformations following the MetRS/cupin-catalyzed reactions in several other pathways. ,, Indeed, we observed that strain Δ afn7 produced approximately 70% less 1 relative to the parental strain and accumulated 5 , indicating the incomplete conversion of 5 to the final product (Figure c). All our attempts to express soluble Afn7 were fruitless.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that putative FAD-dependent oxidoreductase Afn7 could be responsible for this step, catalyzing a C–N bond cleavage reaction utilizing 12 (Figure S15). Homologues of Afn7 have been shown to catalyze analogous transformations following the MetRS/cupin-catalyzed reactions in several other pathways. ,, Indeed, we observed that strain Δ afn7 produced approximately 70% less 1 relative to the parental strain and accumulated 5 , indicating the incomplete conversion of 5 to the final product (Figure c). All our attempts to express soluble Afn7 were fruitless.…”
Section: Resultsmentioning
confidence: 99%
“…zinone biosynthesis, the flavin-dependent oxidase Apy10 oxidizes the CÀ N bond on the other side of the NÀ N bond in the hydrazine intermediate DABA-Ala to give l-2-amino-4hydrazineylbutanoic acid (l-AHBA), which is the core precursor of the dihydropyridazinone scaffold. [36] These observations collectively indicate that either the hydroxylamine or amino acid parts of hydrazines can be integrated into the final products, and the site-selective CÀ N bond cleavage step is the major pathway-branching point that dictates their shapes. The released aldehydes (e. g., AASA from Lys-Gly, Lys-Glu) or α-keto acids (e. g., pyruvate from DABA-Ala) are the direct precursors of the corresponding amino acids and would be recycled by primary metabolism to serve as nitrogen carriers in hydrazine biosynthesis.…”
Section: The Branching Point: Site-selective C-n Bond Cleavage Of Hyd...mentioning
confidence: 98%
“…[22] Biochemical experiments have almost entirely elucidated the biosynthetic pathway of actinopyridazinone (apy), including the unique heterocyclization mechanism employing a distinctive carrier protein (Figure 7). [36] Similar to spb, tri, and aza, the hydrazine intermediate DABA-Ala undergoes oxidative CÀ N bond cleavage mediated by the FADdependent oxidase Apy10 to yield l-AHBA. Importantly, the regioselectivity of the CÀ N bond oxidation differs from that in HAA biosynthesis, leaving the NÀ N bond intact in the side chain of l-DABA.…”
Section: Construction Of Nà N Bond-containing Heterocyclesmentioning
confidence: 99%